Queuing for Surgery: Is the U.S. or Canada Worse Off? - Hamilton, Barton H.; Ho, Vivian; Goldman, Dana P. (The Review of Economics and Statistics, 2000)
Restricted government spending along with universal health insurance has led to longer queues for surgical procedures in Canada versus the United States. Yet it is unclear whether these treatment delays affect health outcomes. This paper tests this hypothesis by comparing the determinants of wait time for hip-fracture surgery and its impact on postsurgery length of stay and inpatient mortality in Canada and the United States. Hazards for surgery/no surgery and discharge alive versus dead are modeled using a competing-risks model. Day of the week of admission is used to help identify the surgery wait-time distribution. We control for unobserved (to the econometrician) health status which may affect wait times and outcomes by assuming a semiparametric distribution for unobserved heterogeneity. We find that predicted hazards for inpatient mortality are virtually identical in Canada and the United States. Yet wait times for surgery are longer in Canada, and surgery delay has a significant impact on postsurgery length of stay in both countries. However, the magnitude of this effect is small relative to other patient and hospital-specific factors. Focusing attention on treatment delays as a weakness in the Canadian health care system may be misleading policymakers from hospital-specific inefficiencies that may have more-important implications for health care costs and patient welfare. © 2000 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology